Platelet-rich Plasma use for facial rejuvenation: a clinical trial and review of current literature - Banihashemi , Mahnaz; Zabolinejad, Naghmeh; Salehi , Maryam; Hamidi Alamdari, Daryoush; Nakhaizadeh , Solmaz (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Several studies have shown beneficial effects for Platelet-rich plasma (PRP). We aimed to assess the efficacy of pure PRP injection for facial rejuvenation in Iran.Methods:  30 female consecutive participants were injected with PRP in two sessions with 3 month interval. Evaluations were performed by comparing the pre- and post-improvement measurements of skin scan, before after photography by participants, therapeutic physician and blindly by a second dermatologist.Results: In 3 and 6 months follow-ups respectively,  moderate to excellent improvement in periorbital dark circles (47.8,60.9%), periorbital wrinkles (73.9%,78.3%), nasolabial fold (52.2%,56.6%) and skin rigidity (52.3%,60.9%)  reported by patients, was statistically significant only for dark circle(P value 0.031). Moderate to good improvement in periorbital dark circles (47.9%,74%), periorbital wrinkles (39.1%,43.5%)and nasolabial folds (4.3% ,13.1%)  demonstrated by therapeutic physician‘s evaluation , was statistically significant for dark circle (P value 0.008) and nasolabial folds (P value 0.025). Moderate to good improvement in periorbital dark circles (34.8%, 52.2%), periorbital wrinkles (26.1%, 34.8%) and nasolabial folds (4.4%, 13%)   by second dermatologist, was statistically significant for dark circle (P value 0.025).Conclusion: Face rejuvenation with PRP is a promising and noninvasive technique with best results observed in improving periorbital dark circles and wrinkles.